(untitled) (Journal Of Educational and Psychological Researches, 2019)
Abstract The aim of the present research is to identify the test wisdom and the preoccupation with learning and psychological tension among postgraduate students at the University of Samarra according to the variables of the department, gender, age, and employee or non-employee, and revealing the relationship between the test wisdom and the preoccupation with learning and psychological tension. The research sample consisted of (75) students randomly selected from postgraduate students at the college of Education. The researcher applies test –wisdom of (Mellman & Ebel) and measurement of preoccupation with learning prepared by (Al-zaabi 2013) also, the researcher used the scale of the psychological stress by (Abu Assaad 2011). To process the collected data, the researcher used frequencies, averages, standard deviations, T-test, Persson correlation coefficient, analysis of the mono-variance, the coefficient of Schiffe and correlation coefficient (Kendalls tau_b). The results reached that the study sample has a good level of probationary wisdom with differences of statistical significance according to the variable of the department in favor of the students of the department of Arabic language. In addition, there were no statistically significant differences among the variable of sex, age and employee or non-employee variable in regard of test wisdom. The finding found that the study sample was characterized by an average level of preoccupation with learning, with no significant statistical differences according to the department, gender, age, and employee or non-employee variable in term of preoccupation with learning. The research sample revels a low level of psychological tension with no statistically significant differences according to the department variable, gender, age, and employee or non-employee in regard of psychological tension. There is no significant correlation between the test wisdom of all its strategies and each of the preoccupation with learning and psychological tension. Key words: eligibility test, test-wisdom, engagement, psychological tension